Analytical and computational study of cascade reaction processes in catalytic fibrous membranes. (30th May 2022) - Sitaru, Gabriel; Gekle, Stephan
Abstract: Multistep catalytic reactions use two different catalysts for the A → B and the subsequent B → C reaction, respectively. Often the employed catalysts are chemically incompatible, such as acid–base systems, which prohibits simple mixing in one solution. In this work, we study the efficiency of reactors where the incompatible catalytic sites are immobilized on fibrous membranes. We compare a lattice Boltzmann based solver for the advection–diffusion–reaction equation, a random walk particle tracking method and a simple theoretical model to investigate the reaction efficiency as a function of two dimensionless control parameters: the Péclet and the Damköhler number. We find that, while the efficiency decreases with higher flow speed (due to the reduced reaction time), the total production nevertheless increases due to the higher mass flux in most cases. Our results further show that, even at high flow speeds, spatial proximity of the two catalysts increases reaction efficiency, which supports recent experimental efforts to locate both catalysts on a single fiber in a side-by-side geometry.